Criteria of medical students for the selection of their future clinical specialisation: a cross-sectional survey at the Medical Faculty of Rostock - Gebhard, Anke; Müller-Hilke, Brigitte (GMS Journal for Medical Education, 2019)
Objective: Despite the increase in the number of graduates in Human Medicine, it has been predicted that there will not only be a shortage of doctors, but also a shortage of specialists in Germany for the years to come. At the same time there are only a few studies on the factors that influence medical students in their decision to select a specialty. Against this background, a study was conducted at the Medical Faculty in Rostock, to investigate the criteria for deciding on a later field of specialty.Methods: Conducting focus groups of four to seven participants of each year of study, criteria were determined which seemed relevant to the students during their selection of their specialty field. The interviews were transcribed and the answers of the participants classified in super categories. With the data obtained a questionnaire was prepared and sent electronically to all students of Human Medicine. Via exploratory factor analysis important criteria and their correlations were determined.Results: A total of 421 students took part in the questionnaire (31.4% return) and indicated their own clinical experience, but also patient contact and work-life-balance as important criteria for a future selection of specialty field. 44.8% of the participants had already made their choice of specialty at the time of the query, and this for the most part took place in the clinical study phase and most often for the subjects Internal Medicine (15.3%), General Medicine (14.2%), Pediatrics (12.0%) and Surgery (11.5%). For those students who already had made a decision, the size and complexity of the field as well as the opportunity to be able to build relationships with patients, were decisive for selection. Those still undecided indicated that for their choice of specialty family friendliness of the field, leisure time and esteem from others were important.Conclusions: Our results show that the personal clinical experience can be a decisive influential factor for future specialty selection. Early contact with the different disciplines could therefore be structured as an aid to help in the decision making, in order to break down any apprehensions and to stop a pending deficiency in specialists.